Extirpation of rectum for cancer in patient with decompensated liver cirrhosis and portal hypertension - P. V. Tsarkov; V. M. Lebezev; V. I. Stamov; V. V. Nikoda; A. Yu. Kravchenko; Ye. D. Lyubivy; B. N. Bashankayev; M. A. Danilov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To estimate efficacy of multidisciplinary approach in treatment of patients with rectal cancer together with portal hypertension and liver cirrhosis using the example of clinical case.Original positions. 71 year-old male patient with diagnosed low rectal cancer and concomitant: decompensated liver cirrhosis, portal hypertension with varicose esophageal and stomach veins and hepatocellular failure of class C by Child-Pugh. Patient was treated by simultaneous abdomino-perineal rectal excision with para-aortic lymphadenectomy and retroperitoneal end colostomy, splenectomy, devascularization of the stomach, gastrotomy with stitching of varicose veins at the lower third of the esophagus and the stomach. On the basis of foreign experience, risks of such surgical interventions were analyzed and, based on current clinical case, optimal surgical concept for patients of this category is proposed.Conclusion. Multidisciplinary approach in diversified clinic allows to provide adequate treatment of patients with cancer of the rectum combined with portal hypertension and liver cirrhosis.